RESEARCH IN THE LABORATORY OF THERMOMECHANICS, APPLIED THERMAL ENERGY, AND NANOTECHNOLOGIES - Avsec, Jurij; Novosel, Urška (Journal of Energy Technology, 2024)
This article presents the research work in the Laboratory of Thermomechanics, Applied Thermal Energy, and Nanotechnologies at the Faculty of Energy Technology of the University of Maribor. The most significant work that has been done is presented.